(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Pernicious anaemia often poses diagnostic and therapeutic challenges to the clinician. Herein, we representing a 55 years old lady who presented with anaemia along with its classical symptoms and features of peripheral neuropathy due to Pernicious anaemia associated with Psoriasis and Arthropathy without any association of other autoimmune disorder. She had all objective evidences of autoimmune atrophic gastritis in gastric fundic biopsy and positive anti-intrinsic factor antibody. Treatment with injection vitamin B12 improved the condition rapidly. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 243-245